Membangun Budaya Komunikasi yang Efektif pada PT CP untuk Mendukung Kemajuan Perusahaan - Weruin, Urbanus Ura (Universitas Pahlawan Tuanku Tambusai, 2025)
One important aspect in supporting the progress of the company is building an effective communication culture both between company leaders and between company leaders and employees. In the midst of an increasingly competitive business climate, effective communication between companies and consumers and stakeholders is needed. A good communication culture between companies and consumers is not only aimed at providing fast, accurate, and transparent information about the company's products and activities but also to maintain, care for, maintain, and develop consumer loyalty to the company. Realizing the importance of developing an effective communication culture in the company, we held training on building an effective communication culture to support the company's progress with PT Crown Pratama (CP) as a Community Service (PKM) partner. PT CP is a company engaged in the packaging of various types of sachet sugar to be distributed to customers such as hotels, cafes, restaurants, and airlines. Company activities and company relations with consumers require that company communication with all parties run according to the principles of effective communication such as being accurate, honest, open, transparent, mutually respectful, and dialogical. Through lecture, discussion, QA, and experience sharing methods, this PKM activity is able to improve the culture of effective communication within the company and with other parties who are directly or indirectly related to the company, products, and services of the company.